Electrically Insulating Flexible Films with Quasi‐1D van der Waals Fillers as Efficient Electromagnetic Shields in the GHz and Sub‐THz Frequency Bands. Issue 11 (12th February 2021) - Barani, Zahra; Kargar, Fariborz; Ghafouri, Yassamin; Ghosh, Subhajit; Godziszewski, Konrad; Baraghani, Saba; Yashchyshyn, Yevhen; Cywiński, Grzegorz; Rumyantsev, Sergey; Salguero, Tina T.; Balandin, Alexander A.
Abstract: Polymer composite films containing fillers comprising quasi‐1D van der Waals materials, specifically transition metal trichalcogenides with 1D structural motifs that enable their exfoliation into bundles of atomic threads, are reported. These nanostructures are characterized by extremely large aspect ratios of up to ≈ 10 6 . The polymer composites with low loadings of quasi‐1D TaSe3 fillers (< 3 vol%) reveal excellent electromagnetic interference shielding in the X‐band GHz and extremely high frequency sub‐THz frequency ranges, while remaining DC electrically insulating. The unique electromagnetic shielding characteristics of these films are attributed to effective coupling of the electromagnetic waves to the high‐aspect‐ratio electrically conductive TaSe3 atomic‐thread bundles even when the filler concentration is below the electrical percolation threshold. These novel films are promising for high‐frequency communication technologies, which require electromagnetic shielding films that are flexible, lightweight, corrosion resistant, inexpensive, and electrically insulating. Abstract : Polymer composite films with fillers of exfoliated quasi‐1D van der Waals materials are described. Such composites with low loadings of TaSe3 reveal excellent electromagnetic shielding in the GHz and sub‐THz frequency ranges, while remaining electrically insulating. These novel films are promising for communication technologies, which require electromagnetic shielding films that are flexible, lightweight, corrosion resistant, inexpensive, and insulating.